Internalisasi Nilai Karakter Religius Melalui Kegiatan Khataman Al-Qur’an di SMA Pasundan 1 Bandung - Reinal Muhtarizal Agnyawan; Rahmat Rahmat; Aang Supriatna (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
This study was motivated by the role of schools in addressing juvenile delinquency and promiscuity through the instillation of religious character values within the educational environment. The study aims to describe and analyze the process of internalizing religious character values through the Al-Qur'an completion ceremony at Pasundan 1 High School in Bandung. A descriptive qualitative approach was used, with data collection techniques including observation, in-depth interviews, and documentary analysis. The results indicate that the instillation of religious character is carried out in a structured manner through decentralized Quran recitation sessions in each class every Monday through Friday from 8:30–8:45 a.m. WIB, supported by the practice of bringing a physical copy of the Qur’an, guidelines on hijab etiquette, restrictions on the use of electronic devices, contemplative methods led by Islamic Education teachers to contextualize religious values, and teachers serving as role models. The study concluded that the Qur’an completion (khataman) activity successfully integrated the “Nyantri, Nyunda, Nyakola” philosophy of YPDM Pasundan into the school ecosystem, while also fostering a transformation in students’ motivation toward independent spiritual awareness that arises from their inner needs.